2021
DOI: 10.1177/20571585211032774
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ experiences of simulation-based learning, 12–18 months after the simulation: A qualitative study

Abstract: Simulation-based learning is a learning method used in educational programmes for health professionals. Little is known about nurses’ experiences after a long period of time has elapsed since the simulation. The aim of this study was to describe nurses’ experiences of simulation scenarios and their perceptions of learning 12–18 months after the simulation. An explorative qualitative approach, including three focus-group interviews, was used. A total of 21 nurses participated. Data were collected in September 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Many previous studies support our current findings as they reported comparable pedagogical factors that affect simulation-based learning. 23 , 25 Our students also highlighted the important role of the facilitator in supporting and supervising the sessions, as well as providing immediate feedback at the end of the session. This is consistent with Madsgaard et al.…”
Section: Discussionmentioning
confidence: 95%
“…Many previous studies support our current findings as they reported comparable pedagogical factors that affect simulation-based learning. 23 , 25 Our students also highlighted the important role of the facilitator in supporting and supervising the sessions, as well as providing immediate feedback at the end of the session. This is consistent with Madsgaard et al.…”
Section: Discussionmentioning
confidence: 95%
“…This is crucial as, despite the effectiveness of simulation learning, the associated stress and anxiety may interfere with the learners' memory of their experiences, and that learning can be affected [ 17 ]. In the literature, some participants experienced different stress levels during the simulation situation, while others felt performance anxiety [ 20 ]. Learners may be embarrassed and frustrated when faced with unexpected situations during the simulation scenario [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tactile and visual nature of working with buttons introduces a unique aspect to the learning process, particularly in abstraction and text analysis. According to Solheim and Flo (7), the impact of simulation as a learning method can be long-lasting, with participants remembering the experience for up to 12-18 months after the simulation event. However, the study suggests that not all students are suited for simulation-based learning.…”
Section: The Button -A Cognitive Thinking Toolmentioning
confidence: 99%
“…Simulation, as a teaching and learning strategy, is a well-studied area among nursing students (5) and health professionals (6,7). Nursing students need to learn how to apply classroom learning and theoretical knowledge in different clinical contexts (5), such as dementia care (8), the student's learning environment (9), and patient safety (10).…”
Section: Introductionmentioning
confidence: 99%